Creating a Metadata-Enabled Framework for Resource Discovery in Knowledge Bases - Howarth, Lynne C. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
With the proliferation of digitized resources accessible via Internet and Intranet knowledge bases, and a pressing need to develop more sophisticated tools for the identification and retrieval of electronic resources, both general purpose and domain-specific metadata schemes have assumed a particular prominence. While recent work emanating from the World Wide Web Consortium (W3C) has focused on the Resource Description Framework (RDF), and metadata maps or Acrosswalks” have been created to support the interoperability of metadata standards -- thus converting metatags from diverse domains from simply “machine-readable” to “machine-understandable”-- the next iteration, to “human-understandable,” remains a challenge. This apparent gap provides a framework for three-phase research (Howarth, 2000, 1999) to develop a tool which will provide a “human-understandable” front-end search assist to any XML-compliant metadata scheme. Findings from phase one, the analyses and mapping of seven metadata schemes, identify the particular challenges of designing a common “namespace”, populated with element tags which are appropriately descriptive, yet readily understood by a lay searcher, when there is little congruence within, and a high degree of variability across, the metadata schemes under study. Implications for the subsequent design and testing of both the proposed “metalevel ontology” (phase two), and the prototype search assist tool (phase three) are examined.